Movement of knowledge : medical humanities perspectives on medicine, science, and experience - Hansson, Kristofer, 1976-; Irwin, Rachel Elizabeth; Merton, Charlotte (Nordic Academic Press checkpoint., 2020)
"Medical knowledge is always in motion. It moves from the lab to the office, from a press release to a patient, from an academic journal to a civil servants desk and then on to a policymaker. These movements matter: value judgements on the validity of certain forms of knowledge determine the direction of clinical research, and policy decisions are taken in relation to existing knowledge. The complexity of medical information and its wider effects is the focus of Movement of knowledge. The authors address the pervasive influence of knowledge in medical and public health settings and scrutinize a range of methodological and theoretical tools to study knowledge. They take a multidisciplinary approach to the medical humanities, presenting both contemporary and historical perspectives in order to explore the borderlands between expertise and common knowledge. Medical knowledge is deconstructed, reconstructed, and transformed as it moves between patients, health providers, and society at large. The acceptance or rejection of treatment protocols based on medical facts has a fundamental impact on us all"--Publisher's description